2017
DOI: 10.1002/ange.201612309
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Ligand Perturbations Influence the Reactivity of Manganese(IV)‐Oxo Complexes

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…The energy and intensity of the near-IR absorption band at 940 nm (ε = 250 M −1 cm −1 , assuming 100% formation) is quite similar to that observed for Mn IV -oxo complexes of the N4py, DMM N4py, and 2pyN2Q ligands (λ max = 920 -1180 nm; ε = 179 -290 M −1 cm −1 ; Table 2). 6,26 On the basis of this similarity, and strongly supported by additional data described below, we assign the chromophore formed by the reaction of and its derivatives showed that variations in the energy of this electronic transition arise predominantly from perturbations in Mn−N equatorial bonding. 6,29 As shown in Figure S5).…”
Section: Cyclic Voltammetry Experimentssupporting
confidence: 68%
See 2 more Smart Citations
“…The energy and intensity of the near-IR absorption band at 940 nm (ε = 250 M −1 cm −1 , assuming 100% formation) is quite similar to that observed for Mn IV -oxo complexes of the N4py, DMM N4py, and 2pyN2Q ligands (λ max = 920 -1180 nm; ε = 179 -290 M −1 cm −1 ; Table 2). 6,26 On the basis of this similarity, and strongly supported by additional data described below, we assign the chromophore formed by the reaction of and its derivatives showed that variations in the energy of this electronic transition arise predominantly from perturbations in Mn−N equatorial bonding. 6,29 As shown in Figure S5).…”
Section: Cyclic Voltammetry Experimentssupporting
confidence: 68%
“…25 Analysis of the product of the reaction of [Mn IV (O)(2pyN2B)] 2+ and thioanisole was performed by 1 H-NMR experiments following previously described methods. 6 The only modification was the use of toluene as internal standard, which was added directly to the 1 H-NMR sample before analysis.…”
Section: Product Analysis Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zuschriften most positive potential for all known nonheme Mn IV bis-(hydroxo) as well as Mn IV oxo intermediates. [35] Considering the highly positive reduction potential, we were interested in studying whether complex 2 could be employed for the oxidation of naphthalene.Upon addition of al arge excess of naphthalene to 2 (1.0 mm)i nas olvent mixture of CF 3 CH 2 OH/acetone (1:3 v/v) at À30 8 8C, however, 2 remained intact, and product analysis of the reaction solution confirmed that no products of naphthalene oxidation had been generated.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…ET reduction of 2 was found to be in equilibrium with [Fe II (phen) 3 ] 2+ ,w here the final concentration of [Fe III -(phen) 3 ] 3+ produced in the ET of 2 increased upon increasing the initial concentration of [Fe II (phen) 3 ] 2+ .T he equilibrium constant (K et )w as determined to be 1.38, and the oneelectron reduction potential (E red )o f2 was then determined to be 1.09 Vv s. SCE using the Nernst equation (Figures S8 and S9). [35] Considering the highly positive reduction potential, we were interested in studying whether complex 2 could be employed for the oxidation of naphthalene.Upon addition of al arge excess of naphthalene to 2 (1.0 mm)i nas olvent mixture of CF 3 CH 2 OH/acetone (1:3 v/v) at À30 8 8C, however, 2 remained intact, and product analysis of the reaction solution confirmed that no products of naphthalene oxidation had been generated. [33] The inset shows an expansion of the pre-edge region from 6536 to 6546 eV.…”
mentioning
confidence: 99%